double Wedding Customs of the Lampung Pepadun Community in the Perspective of Islamic Education - Zakia Al Erza, Rahma; Pahrudin, Agus; Anwar, Chairul (CV. Creative Tugu Pena, 2024)
Lampung traditional marriage ceremony, in its implementation, the marriage of the Sungkai Bunga Mayang clan community is carried out by Rasan Sanak or Sembambangan (elopement) and Rasan Tuho or Intar Sapon (parental approval). Lampung traditional wedding traditions are still many people who carry out wedding customs that do not comply with applicable customary regulations. In some Lampung wedding customs, there may be certain practices such as very high dowries, exchange of goods that are not in accordance with Islamic law, or certain traditions. who do not have basic Islamic education. This research aims to: Analyze and describe the implementation of the marriage customs of the Lampung Pepadun community in the Sungkai Bunga Mayang clan from an Islamic education perspective. This research is descriptive in nature which is analyzed qualitatively in order to describe or describe the condition of an object and then analyze it. This research was structured based on field research by collecting data through interviews, observation, documentation and from various literature related to this research study. In carrying out weddings, the people of Lampung Pepadun in the Sungkai Bunga Mayang clan community always preserve and maintain the customs of intar payu, intar bright field, intar bright, intar manum and sebambangan. This form of tradition is in accordance with Islamic education, this is because the marriage customs of the Lampung Pepadun people in the Sungkai Bunga Mayang clan community are the formation of a Muslim personality, both containing teachings about personal or community attitudes and behavior, towards the welfare of individual and collective life, in accordance with Islamic education. which is individual education and community education. Keywords: Wedding Customs of Lampung, Islamic Education, Lampung Pepadun Community